Upaya Peningkatan Produktivitas Karyawan Studi Kasus pada Nola Catering di Kabupaten Bantul - Yanuar Restu Prabowo; Muhammad Subkhan (MANAJEMEN, 2026)
Productivity of employees is one of the key factors determining the success of service-based businesses, including catering enterprises. This study aims to analyze efforts to improve employee productivity at Nola Catering in Bantul Regency. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. The research informant consisted of the business owner who has direct knowledge of the work system and employee management at Nola Catering. The results indicate that employee productivity is influenced by several key factors, namely work skills, work motivation, work environment, leadership, and the task allocation system. Management has implemented several efforts to enhance productivity, including clear task distribution, providing guidance before the production process, offering work incentives, and adjusting the number of workers when orders increase. However, several challenges remain, such as the limited number of workers and the increasing workload when handling large orders. This study concludes that improving employee productivity requires more structured human resource management to continuously enhance service quality and maintain the competitiveness of the business.